Direct auroral precipitation from the magnetotail during substorms. Issue 15 (30th July 2013) - Ashour‐Abdalla, Maha; Schriver, David; Alaoui, Mostafa El; Richard, Robert; Walker, Raymond; Goldstein, Melvyn L.; Donovan, Eric; Zhou, Meng
Abstract [1] In this study, we examine the causes of electron precipitation during a substorm on 15 February 2008 that lead to auroral brightening. We use global kinetic simulations along with spacecraft and ground‐based data. We find ~keV electrons in the region modeled in the simulation precipitate into the premidnight sector at latitudes between 71° and 75° due to two distinct physical processes: (1) higher latitude precipitation due to electrons that undergo relatively rapid non‐adiabatic pitch angle scattering into the loss cone just earthward of a reconnection region, and (2) lower latitude precipitation due to electrons that are more gradually accelerated primarily parallel to the geomagnetic field by Fermi acceleration. These latter electrons enter the loss cone much closer to Earth at ~−15 to −10 RE. The electron precipitation due to the combination of these two mechanisms coincides spatially with observed auroral brightening during the disturbed event.